PELATIHAN KONSEP NILAI UANG BAGI SISWA SMA KRISTOFORUS I JAKARTA - Elsa Imelda; Mohammad Reza Aulia; Najmi Ardhiannisa (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Tarumanagara, 2025)
In the digital economic era, financial literacy is an essential skill that young generations must possess to face future financial challenges. This community service activity, organized by a team from Universitas Tarumanagara, aimed to enhance the financial management understanding of high school students at SMA Kristoforus I Jakarta, with a particular focus on the concept of the value of money and the time value of money. The program was motivated by students' lack of awareness regarding the difference between the value of money today and in the future, as well as a tendency to spend pocket money without adequate financial planning. The activity was conducted in five stages, including material preparation, explanation of the value of money and money circulation control, training on Present Value and Future Value calculations, and real-life case analysis. Using participatory and practical approaches, the program effectively increased students' awareness of the importance of saving, rational money management, and the development of healthy financial habits from an early age. The outcomes of this activity are expected to serve as a foundation for wise and sustainable financial decision-making in the future. ABSTRAK Dalam era ekonomi digital, literasi keuangan menjadi keterampilan penting yang harus dimiliki oleh generasi muda untuk menghadapi tantangan keuangan masa depan. Kegiatan pengabdian kepada masyarakat (PKM) ini dilaksanakan oleh tim Universitas Tarumanagara dengan tujuan untuk meningkatkan pemahaman siswa SMA Kristoforus I Jakarta mengenai pengelolaan keuangan, khususnya konsep nilai uang dan nilai waktu atas uang (time value of money). Kegiatan ini dilatarbelakangi oleh rendahnya kesadaran siswa terhadap perbedaan nilai uang saat ini dan di masa depan, serta kebiasaan menggunakan uang saku tanpa perencanaan yang matang. Program dilaksanakan dalam lima tahap, mulai dari penyusunan materi, penyampaian konsep nilai uang dan pengendalian peredaran uang, pelatihan perhitungan Present Value dan Future Value, hingga analisis kasus nyata. Dengan pendekatan partisipatif dan aplikatif, kegiatan ini berhasil meningkatkan kesadaran siswa akan pentingnya menabung, mengelola keuangan secara rasional, serta membentuk perilaku finansial yang sehat sejak usia sekolah. Diharapkan hasil kegiatan ini dapat menjadi fondasi bagi pengambilan keputusan finansial yang bijak dan berkelanjutan di masa depan.